Do Detainees Plead Guilty Faster?: a Survival Analysis of Pretrial Detention and the Timing of Guilty Pleas - Petersen, Nick (Criminal justice policy review, 2020)
Although numerous quantitative studies have linked pretrial detention to increased conviction rates, the precise mechanisms linking these decisions remain unclear. Qualitative studies shed light on these processes, revealing that many detainees plead guilty quickly to escape the pains of detention, including poor confinement conditions, strained work or family relations, and “dead time.” Moreover, these pressures to plead are often exacerbated by uncertain detention length, time-sensitive “exploding” plea deals, and temporal discounting. Utilizing data on felony defendants from large urban counties between 1990 and 2004, we assess whether pretrial detention accelerates the pace of guilty pleas. Survival analyses indicate that pretrial detainees plead guilty 2.86 times faster than released defendants do, suggesting that pretrial detention is a powerful prosecutorial tool. Moreover, local resources affect case processing time in ways that are consistent with the courtroom workgroup perspective. Implications for public policies and future research are discussed.